MEMBANGUN KINERJA KARYAWAN MELALUI KOMPENSASI, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PERAWAT RSI SULTAN AGUNG SEMARANG - Fidyah Yuli Ernawati; Siti Rochmah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
The purpose of this study was to find out Compensation, Competence, Work Discipline either partially or simultaneously on the performance of nurses at RSI Sultan Agung Semarang. The research method used multiple regression analysis, this study at RSI Sultan Agung Semarang. The results showed that Compensation had a significant positive effect on the performance of RSI Sultan Agung Semarang Employees. Competence also had a significant positive effect on the performance of employees of RSI Sultan Agung Semarang, Work Discipline had a significant positive effect on Employee Performance of RSI Sultan Agung Semarang.